Dysregulation of neuronal nicotinic acetylcholine receptor–cholesterol crosstalk in autism spectrum disorder - Vallés, Ana Sofía (2021)
Fil: Vallés, Ana Sofía. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina